HPLC-MS analysis of Schisandra lignans and their metabolites in Caco-2 cell monolayer and rat everted gut sac models and in rat plasma - Jia-ming Yang; Siu-po P. IP; Hok-keung J. Yeung; Chun-tao Che (Elsevier, 2011)
The absorption profiles of Schisandra chinensis were evaluated using the human Caco-2 cell monolayer and rat everted gut sac models, as well as in rat plasma. By analyzing the chromatographic and MSn characteristics of individual peak acquired by HPLC-DAD-APCI-MSn determination, thirteen lignans were identified as the major in vitro absorbable components of the Schisandra extract. Most of these compounds were also detected and identified in rat plasma after an oral administration of the Schisandra extract, except for angeloyl(tigloyl)gomisin H and angeloyl(tigloyl)gomisin Q, whose structures possess an ester group at the cyclooctadiene ring. In addition, four metabolites, corresponding to the hydroxylation and demethylation products of schisandrin and the hydrolysis derivative of angeloyl(tigloyl)gomisin Q, were tentatively identified. The results demonstrate that Schisandra lignans are the major absorbable components of this crude drug, and hydroxylation, demethylation and hydrolysis are important metabolic transformations of the absorbable lignans.